WHETHER CONTROL OF THE HEAT RATE IN THE TREATMENT OF HYPERTENSION? - S . V. Nedogoda (Российский кардиологический журнал)
In this literature review indicates the importance of monitoring the heart rate in the selection and prescription of adequate antihypertensive therapy.